Pentingnya Penggunaan Bahasa Indonesia Sebagai Alat Komunikasi - R, Rostina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Language as a means of communication means that language is a series of systematic sounds, in the form of symbols, arbitrary, meaningful, conventional, unique, universal, productive, varied, dynamic, humane, and a social interaction tool that replaces individuals in stating something or expressing themselves to interlocutors in a social group as a means of communication and the identity of its speakers. So Indonesian is important to learn, because Indonesian is a unifying language, a guideline for the compilation and use of good and correct language in scientific communication, and to deepen the language in communicating and to be preserved by its native speakers. This language ethics is closely related to the selection of language codes, social norms, and cultural systems that apply in a society. By using language with attention to language ethics, a person's personality will be said to be good.